Kesiapan Digital SMK Pancasila 12 Paranggupito dalam Menghadapi Keterbatasan Akses - Nur Afifah; Zaki Afifi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The transformation of education in the digital era requires schools to be prepared to integrate information and communication technology (ICT) into the learning process. However, not all educational institutions demonstrate equal readiness, particularly schools in remote areas such as SMK Pancasila 12 Paranggupito, which face significant limitations in digital access. This study aims to analyze the ideal standard of digital readiness for schools in addressing such constraints by examining aspects of human resources, infrastructure, policy, digital access, and adaptive capacity. This study is grounded in the concepts of readiness, digital access, and digital divide as proposed by Aydin and Tasci (2005), Davis (1989), and van Dijk (2006), which emphasize that digital readiness is a multidimensional construct. This research employs a qualitative approach with descriptive analysis based on theoretical review and the empirical conditions of the school. The findings indicate that digital readiness is not solely determined by the availability of technology, but also by teachers’ digital competence, policy support, and the institution’s ability to adapt to limitations. The ideal standard of digital readiness includes: (1) adaptive human resources with adequate digital literacy, (2) functional and contextual technological infrastructure, (3) flexible school policies and management, (4) effective utilization of digital access, and (5) adaptive readiness through innovative learning strategies such as blended learning and the use of offline media. The study concludes that the ideal standard of digital readiness for SMK Pancasila 12 Paranggupito is contextual, adaptive, and integrative, emphasizing the optimization of available resources and innovative strategies in overcoming limited digital access. Therefore, the success of digital transformation in education, particularly in remote areas, is more dependent on human and institutional readiness than on technological availability alone